Answer:
The answer is
⇒ answer (d)
Explanation:
* How to simplify the square root
- The square is even root ⇒ because 2 is an even number
- We can'f find square root for negative number,
- we can change the square root by rational exponent 1/2
* Lets look to our problem
- We have √(3^15)
- That means √(3^14 × 3)
- Lets change the square root to √3 to (3)^1/2
∵
![\sqrt{3^(15)}=\sqrt{3^(14)(3)}=(3^(14))^{(1)/(2)}(3)^{(1)/(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8lluqpxmqoff6ejf44q66966m192rekarx.png)
∵ 14 × 1/2 = 7
∵ 3^1/2 = √3
∴
![3^(7)(3^{(1)/(2)})=3^(7)√(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/inw82e35y5t9rpi16m26cwm6922gl7230y.png)
∴ The answer is (d)